Are face transplant candidates choosing autonomously? A preliminary method to evaluate autonomous choosing in psychosocial and bioethical assessments - Farías-Yapur, Anneke (Frontiers in Transplantation, 2024)
This report proposes a framework for evaluating the validity of informed consent and autonomy in face transplant candidates, taking into account the risk of depression and non-compliance. Traditional factors like decisional capacity, disclosure, comprehension, voluntariness, and agreement are insufficient for assessing valid informed consent in individuals whose self-worth relies on public perception, potentially leading to self-harm if societal worth is undermined. Reliance on self-esteem, rather than inherent personal value, poses risks of depression, poor treatment adherence, and deferential vulnerability. We suggest a qualitative analysis of self-worth, self-esteem, self-trust, and self-respect to better assess the autonomy of face transplant candidates in their decision-making process.